Burnout profiles among French workers in health units for inmates: results of the EHCAU study - Stéphanie Boulier; Cédric Baumann; Hélène Rousseau; Pierre Horrach; Stéphanie Bourion-Bédès (BMC Health Services Research, 2021)
Abstract Background Health care personnel who work in penitentiary environments are at risk of burnout due to a variety of factors. Latest research have brought forward a classification system consisting of five burnout profiles on a continuum between engagement and burnout. The objective of this study was to measure the prevalence of these profiles among professionals working in French health units providing health services for inmates according to the three levels of care and to investigate their characteristics to propose appropriate management and prevention approaches. Methods This study involved a cross-sectional analysis of data from the Evaluation of Health CAre in Units for inmates (EHCAU) study, a multicentric cohort study of professionals practising in health units for inmates in eastern France. Burnout was assessed by the Maslach Burnout Inventory (MBI) at the levels of emotional exhaustion, depersonalization and personal accomplishment. Job conditions and characteristics were measured using the Karasek Job Content Questionnaire and the Effort-Reward Imbalance Questionnaire. Data on sociodemographic characteristics and self-reported health status were also collected. Differences between MBI profiles were identified using Fisher’s exact test and the Wilcoxon test. Results Of the 350 professionals surveyed, 150 responded (42.9%). The most frequent profiles were ineffective (36.9%) and engagement (34.8%). The burnout (7.8%), overextended (15.6%) and disengaged (5.0%) profiles made up the remaining quarter. Significant differences in the burnout profiles were observed in regard to professional occupation (p = 0.01), irregular eating hours (p = 0.04), history of complaint procedures (p = 0.05), anxiety (p < 0.0001), depression (p < 0.0001) and the mental component of self-reported quality of life (p < 0.0001). Conclusions These results confirm that special attention should be given to professionals working in these challenging settings. The results have important implications for theory and research and for more customized approach interventions. Trial registration ID RCB: 2018-A03029–46.